THE RELATIONSHIP OF SONOGRAPHIC SIZE OF THE UTERUS AND OVARIES IN DIFFERENT PHASES OF THE MENSTRUAL CYCLE WITH INDICATORS OF SIZE AND STRUCTURE OF THE BODY IN PRACTICALLY HEALTHY GIRLS OF ECTOMORPHIC SOMATOTYPE - Cherkasova L.А. (World of Medicine and Biology, 2015)
Investigated size of uterus and ovaries in girls of different somatotypes form different by strength, number and quality correlation communications with anthropo-somatometric parameters that can be used as a model of prediction constitutional morpho-functional characteristics organs of female reproductive system in choosing the adequate means and methods of diagnosis, prevention and treatment. Aim of our work – identify features connections of sonographic indicators of uterus and ovaries with anthropometric, somatometric parameters and component composition of body weight in practically healthy urban girls from Podillya with ectomorphic somatotype in different phases of the menstrual cycle. Materials and methods From data bank Scientific and Research Center Vinnitsa National Medical University named after Pirogov taken initial performance of ultrasound examination of the uterus (body length, neck length, width, anteroposterior size, thickness of endometrium and myometrium) of 108 healthy urban girls from Podillya aged from 16 to 18 years in different phases of the menstrual cycle. Anthropometric survey of girls conducted by the scheme V.V. Bunak. Somatotypes of girls we determined by the method of J. Carter and B. Heath, component composition and body mass - by the method of J. Matiegka and the American Institute of Nutrition. Determination of the strength and direction of relations between sonographic indicators of uterus and ovaries and anthropo-somatometric indicators of girls with ectomorphic somatotype (n = 20) conducted in license statistical package "STATISTICA 6.0", right of use which belongs to SRC Vinnitsa National Medical University named after Pirogov, license № BXXR901E246022FA) using Spearman nonparametric statistics. Results. Discussions In girls with ectomorphic somatotype in most of sonographic size of the uterus and in some sizes of ovaries identified significant correlations with anthropo-somatometric parameters and component composition of body weight during the different phases of the menstrual cycle. During all phases of the menstrual cycle observed similarity connections both by strength, number and their direction. Compared with a group of girls mesomorph correlation communications in girls ectomorphs dominated by their strength, the number (by covering, the transverse dimensions and indicators component composition of body weight) and match by their direction. Width, thickness and volume of the left ovary and thickness of the right ovary identified during the ovulation phase have no statistically significant correlations with any anthropo-somatotypological parameter or index component composition of body weight. In girls mesomorph absence of these correlations observed in all phases of the menstrual cycle.